PSIKOANALISIS SIGMUND FREUD DALAM ANIME ONE PIECE KARYA EIICHIRO ODA - Moch Mukhlas; Sri Yanuarsih; I Wayan Letreng (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This study investigates the internal psychological composition of key characters in the anime One Piece, focusing on the Skypiea arc, by employing Sigmund Freud’s psychoanalytic theory. Utilizing a qualitative descriptive method, the research centers on five major characters: Monkey D. Luffy, Enel, Nami, Sanji, and Gan Fall. These figures were chosen due to their significant influence on the plot and the evident psychological complexity they display throughout the storyline. The data were collected through non-intrusive observation of episodes 185 to 192, emphasizing character dialogue, behavior, and interactions that represent the Freudian personality structures of Id, Ego, and Superego. The analysis shows that Enel predominantly operates under the influence of the Id, marked by his selfish desires, aggressive tendencies, and disregard for ethical boundaries. On the other hand, Luffy and Usopp are characterized by their use of the Ego, navigating challenging situations with rational judgment and emotional control. Meanwhile, Nami and Gan Fall exemplify the Superego, guided by moral values, compassion, and a strong sense of duty. These portrayals underline the psychological depth embedded in the anime’s narrative. The research highlights the potential of anime as a medium for scholarly exploration, particularly within literary and psychological studies. It affirms that popular visual culture, such as One Piece, can reflect intricate human behavior and mental processes. Therefore, this study contributes to expanding the academic scope of literary psychology and invites further interdisciplinary investigation.